THE ROLE OF TRANLATION IN BRIDGING ESAT-WEST CULTURAL DIFFERENCES - Maratova Farangiz Xasan qizi; Komiljonova Mavlyuda Abduvalievna (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Translation is a complicated process. It causes major and particular difficulties. Translators and interpreters need know some strategies, methods and tactics in order to cope with the task. Some necessary strategies, methods and tactics help translators and interpreters and play significant role in translation process. It goes without saying that a translator’s work is difficult enough and there are no certain prescribing rules for translation. In his/her work a translator faces different problems arising from grammatical, syntactical, and lexical structures.